SUFFRAGE MOVEMENT IN KATJA VON GARNIER'S IRON JAWED ANGELS MOVIE (2004): A SOCIOLOGICAL APPROACH - HERMANTO, ZOUVAN (2011)
The object of this research is the movie entitled Iron Jawed Angels by Katja Von Garnier. The major problem of this study is "how suffrage movement is reflected in Iron Jawed Angels (2004) by Katja Von Garnier" based on a Sociological Approach. The researcher employs qualitative method; the researcher uses two data sources, namely primary and secondary data source. The primary data source is the movie itself while the secondary data source is the other sources related to the analysis such as script, books, journals, articles, and movie review. The method of data collection is library research and the technique of data collection is note taking and scene capturing. The study comes to the following conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, plot, point of view, setting of place and time, mise-en- scene, cinematography, editing, and the other technical elements have the unity and successfully relate to one another then finally are formulated into good quality of a movie. Second, based on the Sociological analysis, it is the phenomena in American society in the early twentieth century, the political activists Alice Paul and Lucy Burns by using peaceful and effective strategies, tactics, and dialogues to revolutionize the American women's suffrage movement to grant women the right to vote